DEMOGRAPHIC ANALYSIS OF POPULATION OF UZBEKISTAN USING DATA SCIENCE TOOL PANDAS - Meliboev, Azizjon; Asqarov, Elbek; Azizbek, Naraliyev (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
The purpose of this study is to use the data science tool Pandas to perform a demographic analysis of the Uzbek population. We will investigate important demographic parameters as age distribution, gender ratio, population density, urban vs. rural population distribution, and population growth trends over time by utilizing Pandas’ data manipulation and analysis capabilities. In order to produce insightful findings, the analysis will entail importing population databases, cleaning and preparing the data, and doing exploratory data analysis (EDA). The study will provide a thorough grasp of Uzbekistan’s demographic structure by identifying patterns and trends within the country’s population through statistical metrics and visualization.